2021
DOI: 10.2147/oaem.s321365
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Intubation Sequence: 4-Year Experience in an Emergency Department

Abstract: Background:The rapid intubation sequence is advanced airway management that effectively ensures an adequate supply of oxygen in critically ill patients. The medical personnel in the emergency department performed this procedure. Objective: To describe the main characteristics of the rapid intubation sequence in an emergency department of a high complexity hospital. Methods: This is a descriptive, cross-sectional, retrospective study. We included all older patients with a rapid intubation sequence requirement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Another recent study from Columbia reported that EM residents only performed 1.3% of intubations, and the remaining were performed by more experienced physicians. This study reported complications in 9% and an FPS of 90.5% [ 13 ]. A multicenter observational study conducted across 11 Irish EDs reported that 90% of intubations were performed by physicians at the registrar level.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study from Columbia reported that EM residents only performed 1.3% of intubations, and the remaining were performed by more experienced physicians. This study reported complications in 9% and an FPS of 90.5% [ 13 ]. A multicenter observational study conducted across 11 Irish EDs reported that 90% of intubations were performed by physicians at the registrar level.…”
Section: Discussionmentioning
confidence: 99%